Effect of Crack Propagation on Mining-Induced Delayer Water Inrush Hazard of Hidden Fault. (12th August 2021) - Du, Yanhui; Liu, Weitao; Meng, Xiangxi; Pang, Lifu; Han, Mengke
Abstract : Hidden faults in deep coal seam floor threaten the exploitation of coal resources. Under the influence of mining and water confined in the floor, the cemented filler in the hidden fault will be eroded by water flow, in order to investigate the fracture characteristics and water inrush risk of hidden faults in floors above confined aquifer. Using the 27305 working face as geological background, the influence of the seepage scouring filler on the mechanism of water inrush from hidden faults was assessed by developing a stress-seepage coupling model and employing the finite difference method to simulate the seepage process of hidden faults under the combined action of high ground stress and high confined water. The evolution of seepage, shear stress, and plastic zone was also assessed. The influence of the hydraulic pressure of the aquifer and the thickness of a waterproof rock floor on the formation of the water inrush pathway was analyzed. Results indicate that (1) under the influence of mining, the hidden fault experienced the change process of stress stability, stress concentration, and stress release. The shear stress increases first and then decreases. The compressive stress decreases gradually due to stress release. (2) Water inrush disaster will not occur immediately when the working face is above the hidden fault. The delayed water inrush occurs in the mined-out area when the working face advances to 160 m, the floor failure zone is connected with the hidden fault failure zone, and the delayed water inrush channel is formed. (3) With the mining advances, the water pressure of aquifer is the same. The larger-angle fault leads to the thinner thickness of floor aquifer. The greater the influence of hidden fault on coal seam mining, the higher the danger of water inrush.